Study on the performance characteristics of erbium-doped fiber amplifier for C and L-band: article - Sobrattee, Mohamed Arshaad (Faculty of Electrical Engineering, 2010)
Performance of Erbium-doped fibre amplifier is theoretically investigated using 980nm bidirectional pumping in a single-pass configuration. The optimum length of EDF in L-band and C-band is determined in this investigation. For the L-band, the optimum length of EDF was found to be 10m and for C-band, the optimum length was observed to be from 4m to 8m. The bidirectional pumping architecture was chosen over other architectures, such as forward and backward pump because it exhibits the highest possible gain (in dB). At input signal power of -20dBm, a maximum signal gain of 39.55dB is obtained at 1530nm. Moreover, the noise figure recorded is less than 6.78dB within the wavelength region from 1520 to 1610nm.